Exploring structural interactivity in online newspapers: a look at the greek web landscape - Veglis, Andreas A.; Spyridou, Lia Paschalia (My University, 2008)
As the online news industry has completed its first decade of existence, online newspapers are moving beyond the realm of 'shovelware' to produce news marked by increased interactivity, content richness and user control. Content originality and the advantages provided by technology are said to lie at the core of efficient online news production. This paper examines the development of online newspapers in terms of exploiting the structural interactive features available today. Drawing upon quantitative research, it is argued that in the Greek online press the range of possible forms and expressions of interactivity are limited and uneven. The dominant journalistic culture of Greece -in combination to political and cultural traits of the country -are assumed to hinder the expected development of Web publishing.
Keywords: Journalism; Web publishing; Newspapers